SHORT-TERM FINANCIAL PLANNING AND SIMPLE INVESTMENT EDUCATION FOR THE WELFARE OF MSME OWNERS IN SURABAYA - Ratih Dewi Titisari Haryana; Annisah Febriana (Pedagogic Research-Applied Literacy Journal, 2024)
MSMEs play a vital role in the regional economy but still face challenges such as low financial literacy and limited understanding of investment. These conditions lead to weak financial planning and poor welfare for business actors. This community service activity aims to improve MSME owners' understanding of short-term financial planning and simple investment as an effort to strengthen business financial resilience. The implementation method used an educative-participatory approach through interactive workshops, discussions, case studies, and brief mentoring conducted at the Gunung Anyar Culinary Tourism Center in Surabaya. The results showed an increase in participants' understanding of separating personal and business finances, cash flow management, simple financial recording, and the introduction of low-risk investment instruments. Participant satisfaction surveys based on material quality, delivery methods, and activity benefits showed a very high level of satisfaction. Overall, this activity is considered effective and relevant in supporting more planned and sustainable MSME financial management.